Intracellular Zn(2+) Signaling Facilitates Mossy Fiber Input-Induced Heterosynaptic Potentiation of Direct Cortical Inputs in Hippocampal CA3 Pyramidal Cells - Eom, Kisang (J Neurosci, 2019)
Repetitive action potentials (APs) in hippocampal CA3 pyramidal cells (CA3-PCs) backpropagate to distal apical dendrites, and induce calcium and protein tyrosine kinase (PTK)-dependent downregulation of Kv1.2, resulting in long-term potentiation of direct cortical inputs and intrinsic excitability (LTP-IE). When APs were elicited by direct somatic stimulation of CA3-PCs from rodents of either sex, only a narrow window of distal dendritic [Ca(2+)] allowed LTP-IE because of Ca(2+)-dependent coactivation of PTK and protein tyrosine phosphatase (PTP), which renders non-mossy fiber (MF) inputs incompetent in LTP-IE induction. High-frequency MF inputs, however, could induce LTP-IE at high dendritic [Ca(2+)] of the window. We show that MF input-induced Zn(2+) signaling inhibits postsynaptic PTP, and thus enables MF inputs to induce LTP-IE at a wide range of [Ca(2+)](i) values. Extracellular chelation of Zn(2+) or genetic deletion of vesicular zinc transporter abrogated the privilege of MF inputs for LTP-IE induction. Moreover, the incompetence of somatic stimulation was rescued by the inhibition of PTP or a supplement of extracellular zinc, indicating that MF input-induced increase in dendritic [Zn(2+)] facilitates the induction of LTP-IE by inhibiting PTP. Consistently, high-frequency MF stimulation induced immediate and delayed elevations of [Zn(2+)] at proximal and distal dendrites, respectively. These results indicate that MF inputs are uniquely linked to the regulation of direct cortical inputs owing to synaptic Zn(2+) signaling. SIGNIFICANCE STATEMENT Zn(2+) has been mostly implicated in pathological processes, and the physiological roles of synaptically released Zn(2+) in intracellular signaling are little known. We show here that Zn(2+) released from hippocampal mossy fiber (MF) terminals enters postsynaptic CA3 pyramidal cells, and plays a facilitating role in MF input-induced heterosynaptic potentiation of perforant path (PP) synaptic inputs through long-term potentiation of intrinsic excitability (LTP-IE). We show that the window of cytosolic [Ca(2+)] that induces LTP-IE is normally very narrow because of the Ca(2+)-dependent coactivation of antagonistic signaling pairs, whereby non-MF inputs become ineffective in inducing excitability change. The MF-induced Zn(2+) signaling, however, biases toward facilitating the induction of LTP-IE. The present study elucidates why MF inputs are more privileged for the regulation of PP synapses.